Pengaruh Literasi, Promosi dan Religiusitas terhadap Keputusan Masyarakat Menggunakan Produk Bank Syariah di Desa Petaling Banjar Kecamatan Mendo Barat Kabupaten Bangka - Gita Safitri Rahmadani; Ahmad Irvani; Feby Ayu Amalia (JYRS: Journal of Youth Research and Studies, 2023)
Until now, in Indonesia itself it is still dominated by conventional banks, this indicates that people prefer to use conventional bank products. Literacy, promotion and religiosity are factors that can influence people's decision-making behavior. Among all the factors mentioned, each has quite diverse views and assessments. This research aims to analyze the influence of literacy, promotion and religiosity on people's decisions to use sharia banking products. This type of research is field research with a quantitative approach. The data used are primary and secondary data. The population in this study was 3,489 people with a sampling technique, namely random sampling technique and sample determination using the Taro Yamane formula for 100 respondents. With data analysis techniques using validity tests, reliability tests, classical assumption tests, multiple regression tests and hypothesis tests. Data processed using the SPSS version 25.0 application. The results of this research show that literacy has a positive and significant effect on customer decisions in West Mendo District, Bangka Regency with tcount (3.775) > t- table (1.66055), so that H0 is rejected and H1 is accepted with a significance value of (0.000). Promotion also has a positive and significant effect on customer decisions in West Mendo District, Bangka Regency with tcount (2.718) > t-table (1.66055), so that H0 is rejected and H1 is accepted with a significance value of (0.008). Religiosity also has a positive and significant effect on customer decisions in West Mendo District, Bangka Regency with a t-count of 2.406 > t-table (1.66055), so that H0 is rejected and H1 is accepted with a significance value of (0.018). Simultaneously Literacy and Promotion have a significant effect on customer decisions with the Fcount value (67.334) > F-table value (2.70), so that H0 is rejected and H1 is accepted or if you see a significant value of 0.00 < 0.05.